Multidisciplinary management of extensive cervical lymphatic malformations and epiglottic cyst in a neonate: a case report and review of perioperative strategies - Cai, Yuzhu; Zhang, Lingli; Wang, Jun; Sun, Yingying (Frontiers in Pediatrics, 2025)
Lymphatic malformations (LMs) are rare congenital anomalies that can cause life-threatening airway obstruction in neonates, particularly when located in the cervicofacial region. The coexistence of lymphatic malformations with an epiglottic cyst further exacerbates airway compromise, posing significant diagnostic and therapeutic challenges. We report the case of a 27-day-old neonate with extensive cervical lymphatic malformations and an epiglottic cyst causing severe airway obstruction. Timely intervention, including laser ablation of the epiglottic cyst and sclerotherapy for the lymphatic malformations, was successfully performed under general anesthesia. Perioperative management emphasized safe airway control and meticulous surgical planning. Postoperative outcomes were favorable, with significant reduction in lymphatic malformations size and resolution of airway obstruction after additional sclerotherapy sessions. This case underscores the importance of a multidisciplinary approach, combining advanced imaging, innovative airway management techniques, and minimally invasive procedures, to achieve optimal outcomes in complex neonatal airway and vascular anomalies.